2011
DOI: 10.1097/mog.0b013e3283423f20
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell therapy of intestinal disease: are their effects systemic or localized?

Abstract: Purpose of review Stem cell therapy for intestinal diseases is an emerging area in clinical gastroenterology. We will review recent literature regarding mesenchymal stem cells (MSCs), which have been utilized in preclinical models and are now headed for clinical trials in several gastrointestinal diseases including inflammatory bowel disease. Recent findings Important studies over the last 2 years have made significant inroads into understanding the mechanisms of action of these cell types. The two major com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 45 publications
(41 reference statements)
0
20
0
Order By: Relevance
“…The immature intestine is thought to respond to injury with excess inflammation, which is likely the final common pathway in the pathogenesis of NEC (1-3). One may speculate that the anti-inflammatory effect of hBM-MSCs might have played a role in the favorable response achieved in the present study (31)(32)(33). The attenuation of the histopathological damage and protection of the intestine from severe damage was attributable to the regenerative effects of the MSCs.…”
Section: Discussionmentioning
confidence: 63%
“…The immature intestine is thought to respond to injury with excess inflammation, which is likely the final common pathway in the pathogenesis of NEC (1-3). One may speculate that the anti-inflammatory effect of hBM-MSCs might have played a role in the favorable response achieved in the present study (31)(32)(33). The attenuation of the histopathological damage and protection of the intestine from severe damage was attributable to the regenerative effects of the MSCs.…”
Section: Discussionmentioning
confidence: 63%
“…It is also reported that EGR-1 plays an indispensable role in the regulation of platycodon D-induced cell death and the 1, 25D3-induced cessation of cell proliferation, which is characteristic of the terminal stage of differentiation of these cells (93,94). EGR1 and WT1 are structurally related transcription factors and bound to quite similar DNA sequences (95). This gives us a revelation that down-regulating the expression of WT1 can upregulate the expression of EGR1.…”
Section: Pathogenesis Mechanism Of Aml By Egr1mentioning
confidence: 86%
“…It has been discovered in allograft studies conducted with rats that MSCs immigrate to the area of rejection and settle there after infusion [16]. MSCs are found to have improved the intestinal damage in studies concerning inflammatory bowel disease [17].…”
Section: Discussionmentioning
confidence: 99%